2019
DOI: 10.1158/0008-5472.can-18-2231
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized MRI Visualizes Warburg Effects and Predicts Treatment Response to mTOR Inhibitors in Patient-Derived ccRCC Xenograft Models

Abstract: The ever-changing tumor-microenvironment constantly challenges individual cancer cells to balance supply and demand, presenting tumor vulnerabilities and therapeutic opportunities. Everolimus and temsirolimus are inhibitors of mTOR (mTORi) approved for treating metastatic renal cell carcinoma (mRCC). However, treatment outcome varies greatly among patients. Accordingly, administration of mTORi in mRCC is diminishing, which could potentially result in missing timely delivery of effective treatment for select pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 30 publications
(37 reference statements)
2
41
0
Order By: Relevance
“…The proapoptotic effect of everolimus combined with paclitaxel has been successfully shown for HeLa and SiHa cell lines. In addition, it has been demonstrated that both compounds inhibit the PI3K/AKT/mTOR pathway (210).…”
Section: Mtorc1 As a Therapeutic Targetmentioning
confidence: 99%
“…The proapoptotic effect of everolimus combined with paclitaxel has been successfully shown for HeLa and SiHa cell lines. In addition, it has been demonstrated that both compounds inhibit the PI3K/AKT/mTOR pathway (210).…”
Section: Mtorc1 As a Therapeutic Targetmentioning
confidence: 99%
“…A similar decrease in lactate-to-pyruvate ratios was observed in GS-2 glioblastoma rat models following treatment with Everolimus after seven days [35]. HP-MR also predicts treatment response to mTOR inhibitor (rapamycin) in patient-derived ccRCC xenograft models [36].…”
Section: Assessment Of Different Therapeutic Interventionsmentioning
confidence: 77%
“…In the renal cortex, gluconeogenic enzymes (phosphoenolpyruvate carboxykinase (PEPCK), fructose-1,6-bisphosphatase glucose-6-phosphatase) synthesise glucose-6-phosphate from precursors such as lactate, glutamine, glycerol and alanine (37,44). (mechanistic target of rapamycin) inhibition, a therapeutic target in RCC, can be observed as early as 24 hours after the initiation of treatment in a murine model (52). Initial patient data confirm that hyperpolarised imaging is feasible in patients with RCC and highlight the need for further clinical research to define the future role of this modality in uro-oncological imaging (54).…”
Section: Imaging Glycolysis With [1-13 C]pyruvatementioning
confidence: 90%